The intern [videorecording (DVD)] - Meyers, Nancy; Hathaway, Anne, 1982-; De Niro, Robert; Lavin, Linda, 1937-; Russo, Rene (Warner Home Video, 2016)
Ben Whittaker is a 70-year-old widower who has discovered that retirement isn't all it's cracked up to be. Seizing an opportunity to get back in the game, he becomes a senior intern at an online fashion site, founded and run by Jules Ostin.